RESEARCH AND ANALYSIS MATHEMATICAL MODEL OF THE DEMODULATOR FOR ASSESSING THE INDICATORS NOISE IMMUNITY TELECOMMUNICATION SYSTEMS - Ibrahimov, Bayram; Hashimov, Elshan; Ismayılov, Togrul (Сучасні інформаційні системи, 2024)
The noise immunity indicators of the functioning telecommunication systems in the presence interference sources are analyzed based on the architectural concept of the next and future networks. The object study is the optimal demodulator signal receiver with matched filters. The relevance of this area research is shown. Based on a study algorithms for the operation of a demodulator with matched filters, a new approach to constructing a mathematical model for assessing the noise immunity characteristics receiving traffic messages is proposed. The developed mathematical model takes into account the demodulator synthesis algorithm, effective modulation and coding methods in the detector receiver. The subject of the research is a mathematical model for assessing the noise immunity indicators of the functioning multiservice telecommunication networks. Based on a study of the reliability of the transmission traffic messages, a block diagram of an optimal demodulator signal receiver with matched filters is proposed. The purpose of the research is to develop a new approach to create a mathematical model for assessing the characteristics communication quality and noise immunity telecommunication systems when receiving message traffic packets in a complex signal-noise environment. Based on a mathematical model for assessing the noise immunity indicators of telecommunication systems, important analytical expressions for further research were obtained. As a result of the research, the main conclusions of the study were obtained, which can be implemented and used in multi-service fixed and mobile communication networks to calculate the noise immunity indicators of public telecommunication systems. The rationale for the proposed main stages of the study is given, the results of analytical research and simulation modeling are presented, confirming the validity of the theoretical conclusions made.